2016
DOI: 10.1111/ijfs.13223
|View full text |Cite
|
Sign up to set email alerts
|

Development of a spectroscopic method to determine the content of free radical scavenging compounds and oxidation products in thermally oxidised oils

Abstract: Summary A simple spectroscopic method using 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) was developed to simultaneously monitor the contents of free radical scavenging antioxidants (FRSs) and oxidised lipid products during oxidation through selection of proper solvents. Validation of the DPPH method was conducted in a stripped oil matrix, and practical applicability of the method was tested with heated oils. The absorbance of DPPH in isooctane simultaneously reflected the changing amounts of both FRSs and oxidised li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…To quantify the contents of FRSs or RSOLs in oil samples, the DPPH absorbance was converted to DPPH loss with units of mmol DPPH/g oil sample using the following equation [8,11] : Samples were prepared in triplicate.…”
Section: Modified Dpph Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To quantify the contents of FRSs or RSOLs in oil samples, the DPPH absorbance was converted to DPPH loss with units of mmol DPPH/g oil sample using the following equation [8,11] : Samples were prepared in triplicate.…”
Section: Modified Dpph Methodsmentioning
confidence: 99%
“…Polar compounds, which accelerated the rates of lipid oxidation compared to non-polar compounds, as shown in Figure 1 and 2, induced different profiles of DPPH loss in methanol and in isooctane. Song et al [8] reported that only antioxidants, and not RSOLs, could react with DPPH in methanol, whereas both antioxidants and RSOLs could react with DPPH in isooctane. Rising DPPH loss in isooctane in samples with polar compounds at 60 min could be attributed to the formation of RSOLs.…”
Section: Corn Oil Without Addition Of Antioxidantsmentioning
confidence: 99%
See 3 more Smart Citations